Appreciation of a Child’s Journey: Implementation of a Cardiac Action Research Project - Kate Alexa Dengler; Valerie Wilson; Sarah Redshaw; Gabrielle Scarfe (Nursing Research and Practice)
The aim of this paper is to provide an overview of the phases of the action research process involved in developing, implementing, and evaluating the Heart Beads program. The aim of the project is to enrich the hospital experience of children with cardiac conditions. Heart Beads involves children receiving unique beads specific to each cardiac treatment, procedure or event in recognition of their experiences, and endurance. An action research approach, involving a partnership between clinicians and researchers and emphasising the involvement of patients and their families, was used to guide the Heart Beads program. The project followed the five phases of action research: identification, investigation, program development, implementation, and evaluation. Heart Beads began as a small project which continues to grow in popularity and significance with children at a tertiary paediatric hospital in Sydney, Australia. The program is now being implemented nationwide with the vision that all Australian children hospitalised with cardiac conditions can benefit from Heart Beads.